Qualitative risk assessment of follicle stimulating hormone injectable products. (1st November 2020) - Steinke, Douglas T; Zarroug, Osman H; Mathur, Raj; Kendrew, Helen; Jenkins, Julian
ABSTRACT: Background: Gonadotropin injections for fertility treatment regimens are usually self-injected, typically over 8–12 days during the assisted reproductive technology cycle. Parenteral gonadotropins are available in different formulations and administered through various systems. A user experience study and risk assessment were performed to evaluate different product types for risks to the patient when preparing and administering injections. Methods: Nine women of child-bearing age each prepared and administered injections of six products representing single- and multidose vials of menotropin for reconstitution (Merional® and Menopur®), follicle stimulating hormone (FSH) reusable pen injectors with (Puregon®), and without cartridges (Gonal-f®), and single-use FSH pre-filled pens (Bemfola®). Risk assessments based on user feedback were made with reference to EU regulations for implementing practices for safe use of injectable products. Results: Products requiring reconstitution with diluent in glass ampoules were associated with medium risk for sharps injury and a lower level of user confidence. Pen injectors were considered easy-to-use, with a low risk of sharps injury. Single-use pens were associated with the lowest risk of dosing errors. Conclusions: The study identifies differences in the risks for both sharps injuries and dosing errors between FSH delivery options that practitioners should consider when making a treatment choice.